The Effect of Health Education on The Level of Reproductive Health Knowledge of High School Students - Dina Mariana Larira; Septriani Renteng (USN Scientific Journal, 2020)
As children get older, they experience a transition to adulthood commonly called puberty. Not all the needs of adolescents can be understood well in many ways, especially in terms of reproductive health so that a variety of adolescent problems arise. So, adolescents need knowledge about reproductive health starting when they enter puberty. One of the ways to increase adolescent knowledge about reproductive health is to provide health education to prevent problems related to reproductive health in adolescents. As an effort programmed by the government, one of them is by providing education through counseling activities.This study aims to determine the effect of health education on the level of reproduction health knowledge of adolescent students in grade IX in SMP 09 Kota Kendari. This study uses a pre experimental pretest-posttest design. A sample of 38 respondents was taken in total sampling in class IX. Each respondent was given a questionnaire pretest and counseling was conducted and then each respondent was given a questionnaire posttest. Data analysis was performed paired t test.The results of the study showed a significant difference in the level of knowledge after counseling (p0.05). In the research results obtained the average value on the pretest results is 11.11 then after counseling the average value of the posttest is 11.89. Significant differences in the analysis of the level of knowledge (0.021 0.05). The conclusion of this research is that there is an effect of health education on the level of knowledge of adolescent reproductive health. The researcher suggests that the school conduct a program for adolescent reproductive health counseling in collaboration with health workers and train peer educators and peer counselors to increase adolescent knowledge about reproductive health.Keywords: Counseling , Level of Knowledge, Reproductive Health, Adolescent